A Game Assessment Metric for the Online Gamer - DENIEFFE, D.; CARRIG, B.; MARSHALL, D.; PICOVICI, D. (Advances in Electrical and Computer Engineering, 2007)
This paper describes a new game assessment metric for the online gamer. The metric is based on a mathematical model currently used for network planning assessment. Beside the traditional network-based parameters such as delay, jitter and packet loss, new parameters based on online players' game experience/knowledge are introduced. The metric aims to estimate game quality as perceived by an online player. Measurements can be achieved in real-time or near real-time and could be useful to both online game players and game service providers. In order to validate and calibrate the proposed metric a subjective game quality assessment is also proposed. Two 5-point scales are introduced: a game-quality scale and a game playing-effort scale. The mean average of each scales termed, as Mean Opinion Score (MOS), will indicate the game quality (MOSGQE) and the playing-effort required (MOSGPE). The results obtained using subjective tests are divided in two parts. The first part is used during the development and calibration of the proposed objective algorithm. The second part is used to validate the proposed algorithm. The algorithm's performance can be measured using Pearson correlation between the subjective and objective MOSGQE scores.